A novel, reusable, realistic neurosurgical training simulator for cerebrovascular bypass surgery: Iatrotek® bypass simulator validation study and literature review - D’Andrea, Marcello; Musio, Antonio; Colasanti, Roberto; Mongardi, Lorenzo; Fuschillo, Dalila; Lofrese, Giorgio; Tosatto, Luigino (Frontiers in Surgery, 2023)
Background Microanastomosis is a challenging technique requiring continuous training to be mastered. Several models have been proposed, but few effectively reflect a real bypass surgery; even fewer are reusable, most are not easily accessible, and the setting is often quite long. We aim to validate a simplified, ready-to-use, reusable, ergonomic bypass simulator. Methods Twelve novice and two expert neurosurgeons completed eight End-to-End (EE), eight End-to-Side (ES), and eight Side-to-Side (SS) microanastomoses using 2-mm synthetic vessels. Data on time to perform bypass (TPB), number of sutures and time required to stop potential leaks were collected. After the last training, participants completed a Likert Like Survey for bypass simulator evaluation. Each participant was assessed using the Northwestern Objective Microanastomosis Assessment Tool (NOMAT). Results When comparing the first and last attempts, an improvement of the mean TPB was registered in both groups for the three types of microanastomosis. The improvement was always statistically significant in the novice group, while in the expert group, it was only significant for ES bypass. The NOMAT score improved in both groups, displaying statistical significance in the novices for EE bypass. The mean number of leakages, and the relative time for their resolution, also tended to progressively reduce in both groups by increasing the attempts. The Likert score expressed by the experts was slightly higher (25 vs. 24.58 by the novices). Conclusions Our proposed bypass training model may represent a simplified, ready-to-use, reusable, ergonomic, and efficient system to improve eye-hand coordination and dexterity in performing microanastomoses.